The Effect of Ladder Drill and Zig-Zag Exercises on Footwork Agility in Badminton Players PB. Dahlia Pagaralam - Rajasa, M. Bintang; Manullang, Jujur Gunawan; Putri, Siti Ayu Risma (Physical Education, Health and Recreation Study Program, Universitas Insan Budi Utomo, Indonesia, 2025)
This study aims to determine whether ladder drills and zig-zag exercises affect footwork agility in badminton players of PB. Dahlia Pagaralam. The research method used is an experimental method with a Two-Group Pretest-Posttest Design. The data collection technique involved testing. The sample consisted of all male athletes of PB. Dahlia Pagaralam, totalling 20 athletes, was selected using a total sampling technique. Data were analyzed using hypothesis testing with the t-test. The results for Group 1 showed a t-value = 12.676, which is greater than the critical value (t-table = 1.833). Group 2 showed a t-value of 15.922, which is also greater than the t-table value. This indicates differences between the two exercises in improving agility. To determine which of the two exercises had a greater effect, the mean pretest and posttest scores for Group 1 were 22.40 and 25.70, respectively. For Group 2, the corresponding scores were 19.70 and 22.30. Thus, Group 1 experienced an increase of 3.30, whereas Group 2 increased by 2.60. These results suggest that the ladder drill exercise has a more significant effect on improving badminton footwork agility compared to zig-zag.